2022
DOI: 10.1021/acs.estlett.2c00650
|View full text |Cite
|
Sign up to set email alerts
|

Aging Processes Dramatically Alter the Protein Corona Constitution, Cellular Internalization, and Cytotoxicity of Polystyrene Nanoplastics

Abstract: Humans are exposed to nanoplastics (NPs) through different routes, which raises critical concerns of related health effects. Due to their small sizes, NPs are accessible to the bloodstream and prone to interact with plasma proteins. NPs are susceptible to different aging processes before entering the human body, and it is plausible to evaluate the effect of aging on the physicochemical and biological properties of NPs. Here, we found that ultraviolet (UV) and ozone (O3) aging treatments caused the oxidation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Similarly, Cao et al showed that n-PS MPs/NPs exhibited high surface area and strong binding affinity after being adhered and absorbed by cells, and intensified the Environmental Science: Nano Paper generation of bio-corona, 17 while this adsorption behavior altered the transport, biotransformation and toxicity levels of MPs/NPs. 37 Sun et al also found that both p-and n-PS influenced Arabidopsis thaliana roots, and the p-PS showed more pronounced toxicological effects. This was attributed to the fact that the p-PS stimulated the generation of higher levels of exudates from roots, 29 thus affecting the mobility and uptake of MPs/NPs.…”
Section: Localization and Analysis Of Root Absorption Of Mps/npsmentioning
confidence: 96%
“…Similarly, Cao et al showed that n-PS MPs/NPs exhibited high surface area and strong binding affinity after being adhered and absorbed by cells, and intensified the Environmental Science: Nano Paper generation of bio-corona, 17 while this adsorption behavior altered the transport, biotransformation and toxicity levels of MPs/NPs. 37 Sun et al also found that both p-and n-PS influenced Arabidopsis thaliana roots, and the p-PS showed more pronounced toxicological effects. This was attributed to the fact that the p-PS stimulated the generation of higher levels of exudates from roots, 29 thus affecting the mobility and uptake of MPs/NPs.…”
Section: Localization and Analysis Of Root Absorption Of Mps/npsmentioning
confidence: 96%
“…Once further degrading into nanoplastics, when they contact various biomolecules (e.g., proteins), a biomolecule corona can quickly form and further alter their persistence, bioavailability, and ecotoxicity . In addition, aging processes can alter the protein corona constitution …”
Section: Toxic Effects Of Microplasticsmentioning
confidence: 99%
“…In the ecological environment, diverse biomolecules are found in air, soil, water, plants, animals, and excreta, and the root rhizospheres of plants, water, and sediment also contain a diverse array of microorganisms and secretions that contribute a complex mixture of biomolecules for eco-corona formation. 25 Moreover, environmental factors including temperature, pH, ultraviolet (UV) 23 exposure, radiation, microbial communities, and anthropogenic chemicals greatly influence the properties of ENMs and nano-eco interactions. Recently, Wen et al 23 found that UV and ozone aging treatments oxidize the PS NP surface, and change the physical and chemical properties including particle size and zeta potential, which results in their differential adsorption of plasma proteins.…”
Section: Features In Mediating Nano-bio Interactionsmentioning
confidence: 99%
“…25 Moreover, environmental factors including temperature, pH, ultraviolet (UV) 23 exposure, radiation, microbial communities, and anthropogenic chemicals greatly influence the properties of ENMs and nano-eco interactions. Recently, Wen et al 23 found that UV and ozone aging treatments oxidize the PS NP surface, and change the physical and chemical properties including particle size and zeta potential, which results in their differential adsorption of plasma proteins. Du et al 88 demonstrated that photo-aging alters both the species and abundance of proteins in human bronchoalveolar lavage fluid coronas of PS NPs.…”
Section: Features In Mediating Nano-bio Interactionsmentioning
confidence: 99%
See 1 more Smart Citation